The Efficacy of Hijaiyah Letter Picture Media in Early Arabic Language Acquisition - Fauziyyah, Eva; Ratna Sari, Selvi (LinguaScopes: International Journal of Language Education, 2025)
This study investigates the efficacy of Hijaiyah Letter Picture Media in enhancing early Arabic language acquisition among young children (4-6 years old) within a quasi-experimental design. Building upon the challenges of conventional teaching methods, which often lead to low engagement and retention, this research hypothesizes that interactive visual media can significantly improve letter recognition, pronunciation, and word association. Findings from a simulated intervention demonstrate substantial improvements in the experimental group compared to a control group, evidenced by pre-test and post-test scores. The results align with constructivist and cognitive theories of learning, emphasizing active knowledge construction and multisensory engagement, and underscore the critical role of well-designed visual aids in fostering early language proficiency and motivation.